Ocean acidification alters meiobenthic assemblage composition and organic matter degradation rates in seagrass sediments. (16th July 2019) - Ravaglioli, Chiara; Lardicci, Claudio; Pusceddu, Antonio; Arpe, Eleonora; Bianchelli, Silvia; Buschi, Emanuela; Bulleri, Fabio
Abstract: Seagrass meadows are an important organic matter (OM) reservoir but, are currently being lost due to global and regional stressors. Yet, there is limited research investigating the cumulative impacts of anthropogenic stressors on the structure and functioning of seagrass benthic assemblages, key drivers of OM mineralization and burial. Here, using a 16‐month field experiment, we assessed how meiobenthic assemblages and extracellular enzymatic activities (as a proxy of OM degradation) in Posidonia oceanica sediments responded to ocean acidification (OA) and nutrient loadings, at CO2 vents. P. oceanica meadows were exposed to three nutrient levels (control, moderate, and high) at both ambient and low pH sites. OA altered meiobenthic assemblage structure, resulting in increased abundance of annelids and crustaceans, along with a decline in foraminifera. In addition, low pH enhanced OM degradation rates in seagrass sediments by enhancing extracellular enzymatic activities, potentially decreasing the sediment carbon storage capacity of seagrasses. Nutrient enrichment had no effect on the response variables analyzed, suggesting that, under nutrient concentration unlikely to cause N or P imitation, a moderate increase of dissolved nutrients in the water column had limited influence on meiobenthic assemblages. These findings show that OA can significantly alter meiobenthic assemblage structure and enhance OM degradation rates in seagrass sediments. As meiofauna are ubiquitous key actors in the functioning of benthic ecosystems, we postulated that OA, altering the structure of meiobenthic assemblages and OM degradation, could affect organic carbon sequestration over large spatial scales.